Genetic landscape of phospholamban cardiomyopathies - Elizabeth Vafiadaki; Ishita Chaudhari; Keisha Mireia Soliman; Aristides G. Eliopoulos; Evangelia G. Kranias; Evangelia G. Kranias; Despina Sanoudou; Despina Sanoudou (Frontiers in Cell and Developmental Biology)
Phospholamban (PLN) is a key regulator of cardiac muscle contractility and has become a central focus in the study of cardiac disease. Variants in the PLN gene have been identified in patients with a wide range of phenotypes, including hypertrophic, dilated, and arrhythmogenic cardiomyopathies. The growing number of identified variants highlights the previously underappreciated role of PLN in cardiac pathophysiology. This review offers a comprehensive examination of the genetic landscape of PLN and evaluates the mechanistic effects of specific variants on cardiac function, aiming to uncover potential genotype-phenotype correlations. The rapidly expanding body of knowledge in this area is driving the development of advanced diagnostic and prognostic tools, as well as highly targeted therapeutic strategies. These advances underscore the importance of recognizing PLN’s role in cardiac disease and the value of genetic testing for accurate diagnosis, prognosis, effective management, and early risk prediction for family members.